REVIEW ON ETHNOBOTANICAL STUDIES OF NUTRACEUTICAL PLANT: CAPPARIS SPINOSA L. (CAPER) - S, Manikandaselvi; V, Vadivel; P, Brindha (Asian Journal of Pharmaceutical and Clinical Research, 2016)
Objective: Capparis spinosa L. (Caper) is a perennial spiny bush that bears rounded, fleshy leaves and big white to pinkish-white flowers. It is native to the Mediterranean region and growing wild on walls or in rocky coastal areas throughout India. Even though it has been used in traditional Indian system of medicines for various human diseases, the summation of its medicinal properties is lacking. Hence, the present review focused to provide collective information regarding the medicinal value of C. spinosa. Methods: Literatures were collected from online resources like Scopus, Sciencedirect etc., related to the pharmacological activities of Capparis spinosa and the available information were summarized and given in the review. Results: C. spinosa has anthelminthic, cytotoxic, anti-inflammatory, antiarthritic, antioxidant, antibacterial, antifungal, antiviral, cardiovascular, chondroprotective, antidiabetic, hypolipidemic, antiallergic and antihistaminic, immunomodulatory, anticarcinogenic, and antihepatotoxic activity. The phytochemicals identified in this plant were lipids, alkaloids, glucocapperin, and polyphenols. Conclusion: This review attempts to encompass the available literature on C. spinosa with respect to its pharmacognostic characters, chemical constituents, nutritional characters, various pharmacological activities, traditional uses, and modern use. Keywords: Capparis spinosa L., Caper, Medicinal properties, Nutritional value, Phytochemicals.